Etiology and Treatment of Peri-Implant Soft Tissue Dehiscences: A Narrative Review - Charalampos Kaddas; Eirini Papamanoli; Yiorgos A. Bobetsis (MDPI AG, 2022)
Implant soft tissue dehiscences compromise not only the aesthetics of the supported restorations but implant survival in the long run. The aim of this narrative review was to briefly present the causative factors of buccal peri-implant soft tissue dehiscences (PSTDs), how these are classified, and the current therapeutic approaches. Implant malposition and the thin peri-implant phenotype are the two major determinants for the occurrence of PSTDs, but other risk factors have also been identified. The most common surgical procedure for treating PSTDs is the split-thickness coronally advanced flap combined with either a connective tissue graft or acellular dermal matrix materials. However, depending on the class and subtype of the dehiscence, the combination of surgical techniques with modifications in the restoration may further ameliorate the final result. In general, within a five-year follow-up period, most techniques lead to a satisfactory aesthetic result, although full coverage of the implant/abutment surface is not always achievable, especially in more extended lesions.